Through the eyes of Mary Anne Sadlier: literary scholarship on tales of the Irish female immigrant - Alashjaai, Nouf Fahad M.; Bahar, Ida Baizura; Ching, Florence Toh Haw; Mani, Manimangai (Scientific Research Publishing, Inc., 2024)
This paper focuses on the research problem of how Irish female immigrant characters in selected novels written by Mary Anne Sadlier (1820-1903) face racial prejudice and social struggle while transitioning to their new lives in America. These are overlooked texts on the accounts of 19th-Century Irish female immigrants where previous scholarship has focused on other mainstream issues, namely gender inequality, racism, class-based and social divisions. Nevertheless, the challenges brought by the Great Famine (1845) was crucial in contributing to the recognition of the existence of these Irish female immigrants. The Irish emigration literary studies are an area that has just recently begun to open up to scholarly examination. To date, few examples of scholarly research on the literary portrayals of women focussing on the issue of emigration to America have been published. This paper also discusses the cultural and political aspects that have affected writers in general and, to be specific, Sadlier. Due to the Great Famine, the negative conditions of the Irish women’s lives have been depicted in Western literature. These women had to endure the conditions and work hard to help themselves out of the Great Famine situation in these new countries and environments. From reviews of studies on Sadlier’s writings, it is evident that women are involved in religion, society and politics, unlike before, especially women from England and Ireland. Literary scholarship has shown that Sadlier’s novels have created a literary space for which the Irish migrant women could define who they are and voice out their experiences for themselves leading to the conceptualisation of the Irish female immigrant identity.